(untitled) (Proceedings of Southern Federal University. Philology, 2020)
Based on the errors that many Iranian students of the Russian language make in their speech, the author demonstrates intercultural incompatibilities that cause such errors. In this relation it was focused that, although the wrongful statements are grammatically correct, they are natively and culturally «non normative» and «inappropriate». In this regard the author uses the criterion of different «distribution» rules among different languages. At the end of the article the author concludes that in teaching Russian language to the Iranian students when ignoring the cultural aspects of the language will bring stability of demonstrated errors in the speech of the students. Keywords: linguocultural errors, culture in teaching Russian language, Russian as a foreign language, teaching Russian language in Iran, Persian language. DOI 10.18522/1995-0640-2020-1-167-181